Knowledge and expectations of the accompanying member concerning illnesses and hospitalization of the newborn - Oliveira, Maria da Gloria Machado de; Lopes, Márcia Maria Coelho Oliveira; Lélis, Ana Luiza Paula de Aguiar; Mota, Zélia Gomes; Cardoso, Maria Vera Lúcia Moreira Leitão (Rev Rene, 2014)
This study aimed at describing the knowledge, difficulties and expectations of accompanying members concerning illnesses and hospitalization of the newborn. It is a qualitative study with 11 accompanying members of infants admitted in public hospital, in Fortaleza, CE, Brazil. It consists of semi-structured interviews carried out and recorded in June 2012. It was based on the content analysis that emerged from three categories: knowing the health problems of the newborn, expectations in the hospital context and difficulties faced by accompanying members. It was observed that the accompanying members had limited knowledge about the health conditions that resulted in the hospitalization of the newborn, although there was a professional health team for the guidelines, for the affected needs. Commonly speaking, it expresses limited information, but possible to be understood. It is essential that the health professionals provide to the accompanying members on the disease, treatment and recovery of the newborn so that they can understand the process of hospitalization and provide proper assistance.